Simultaneous detection of carbon monoxide and viscosity changes in cells - Robson,JA; Kubánková,M; Bond,T; Hendley,RA; White,AJP; Kuimova,MK; WiltonEly,JDET (Angewandte Chemie, 2020)
A new family of robust, nontoxic, watercompatible ruthenium(II) vinyl probes allows the rapid, selective and sensitive detection of endogenous carbon monoxide (CO) in live mammalian cells under normoxic and hypoxic conditions. Uniquely, these probes incorporate a viscositysensitive BODIPY fluorophore that allows the measurement of microscopic viscosity in live cells via fluorescence lifetime imaging microscopy (FLIM) while also monitoring CO levels. This is the first example of a probe that can simultaneously detect CO alongside small viscosity changes in organelles of live cells.